Hubungan antara Pola Kelekatan Remaja terhadap Orangtua dengan Kecerdasan Emosi pada Siswa Kelas VII & VIII SMP Negeri 166 Jakarta - popi avati; Nurul Adinigtyas; Rahmah Rahmah (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2018)
Adolescence who have good emotional intelligence will be able to master their minds to focus on things that will only encourage productivity to develop themselves; they will be able to motivate themselves in overcoming the pressure so that they can get through the difficulties and rise again trying to reach back to the ultimate goal and also able to establish good relationships with various parties. The research is focused on the correlation between attachment style with emotional intelligence of adolescence at seventh and eighth grade at SMP Negeri 166 Jakarta. The subjects were 205 students. The sampling techniqueused was  random sampling. The research approaches used are quantitative approach with explanatory survey method (questionaire). Analysis of the data by using Cramer’s V correlation test. The results showed that there is no a significant correlation between  attachment patterns of adolescence with their emotional intelligence with significant value  0,310 > 0,05